Voluntary Social Work as a Paradox - la Cour, Anders; Højlund, Holger (Acta sociologica, 2008)
This article is written as an invitation to sociologists to rethink the concept of voluntary social work. Rather than comprehensive theory, it is an essay seeking to explore new ways of perceiving voluntary social effort. Voluntary work has traditionally been defined according to whether or not the subject of the study is organized and unpaid. However, these formal measures overlook the fact that much voluntary work is provided by people who do not fit the categories, and they fail to recognize the special nature of voluntary social work. In this article, we employ the works of the German sociologist Niklas Luhmann to examine what happens when voluntary social work is constructed as a particular form of care work. In this perspective, all care work is formed in the context of opposing expectation structures, and voluntary work is no exception. On the one hand, we have the expectation structures of the persons involved in care; on the other, the expectations of the administrative system and the political, juridical and economic layers of organization. Our assertion is that voluntary social work is fundamentally paradoxical in nature, and is formed as an impossible compromise between interactional and organizational logic. The question is not how to resolve or dissolve this paradox, but how to render it productive as a certain tension in the opportunity for voluntary work. Before we elaborate this thesis further, however, we briefly outline the background of social work and the reason why, today, it is followed especially closely by the state. This means looking at the way in which the couplings between welfare practice and voluntary work have traditionally been defined. While the article refers only to Danish social policy, very similar tendencies can be observed in many other Western welfare societies (see, for example, Wolch, 1990; Smith and Lipsky, 1993; Eikaas, 2001; Lynn, 2002; Reisch and Sommerfeld, 2003).